2019
DOI: 10.1080/02602938.2018.1564811
|View full text |Cite
|
Sign up to set email alerts
|

Student perspectives on formative feedback as part of writing portfolios

Abstract: Despite the crucial role that students play in formative assessment practices, student perspectives on such practices are relatively under-researched. Through a qualitative analysis of 128 reflection notes written by student teachers of English, this article investigates the students' perceptions of formative feedback as part of portfolio assessment at two teacher education institutions in Norway. As such, it contributes to bridging the gap between research and practice. Students received peer and teacher feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 35 publications
2
24
0
4
Order By: Relevance
“…Finally, for the last point, that is being the kind of feedback considered constructive in English writing. It is in line with Bader et al (2019)Bader et al (2019 opinion that students' positive attitudes towards the portfolio process suggest that students would benefit from more opportunities to revise and resubmit their work and interpreting and implementing feedback in general.…”
Section: Research Question 4 What Do You Think About the Relation Besupporting
confidence: 74%
“…Finally, for the last point, that is being the kind of feedback considered constructive in English writing. It is in line with Bader et al (2019)Bader et al (2019 opinion that students' positive attitudes towards the portfolio process suggest that students would benefit from more opportunities to revise and resubmit their work and interpreting and implementing feedback in general.…”
Section: Research Question 4 What Do You Think About the Relation Besupporting
confidence: 74%
“…The goal of formative feedback is to modify the thinking and behavior of the learner to improve learning (Frank et al 2017). Formative assessment feedback is employed to support learning, aid students to bridge the gap between desired learning objectives and actual level of performance, and it helps students to appreciate the value of high-quality work (Bader et al 2019;Colbran et al 2016;Sadler 1989). Shute (2007, p. 1) states that "formative feedback represents information communicated to the learner that is intended to modify the learner's thinking or behavior for the purpose of improving learning".…”
Section: Formative Feedbackmentioning
confidence: 99%
“…Effective feedback has been documented in research as a facilitator of learning (Aoun et al 2016). It is imperative for both teachers and students to know what constitutes effective feedback, its impact on teaching and learning, its functions, and also their respective roles in the feedback processes (Bader et al 2019). Colbran et al (2016) mentioned that effective feedback provides clarification what is termed as a good performance, it fosters independent studies, and is able to motivate and encourage students to know the gap between knowledge and understanding.…”
Section: Effective Assessment Feedback In Teaching and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…She suggested that instructors should maintain lasting focus on and commitment to portfolios in order to successfully implement portfolio assessment in the ESL classroom. Bader et al (2019) investigated the students' perceptions of formative feedback as part of portfolio assessment in Norway. From the 128 reflection notes written by student teachers of English, they found that students attached great importance to teacher feedback and considered it significant, while students thought the peer feedback lack constructive criticism.…”
Section: Portfolio Assessment On Writingmentioning
confidence: 99%